The Direction of Time (International Journal of Scientific Research and Management (IJSRM), 2020)
An explanation of the direction of time from the past into the future has not yet been possible. With this publication an explanation is given. In general a connection between time and entropy is assumed. Like time, entropy should have only one direction, it should increase. For this purpose the development of space is described with the classical methods of thermodynamics. Furthermore, a closed and thermally insulated container with different temperature ranges is considered: Even if there is no transport of mass or energy across the system boundaries, there is a temperature equalization. This is interpreted as entropy growth. Furthermore, the concentration equalization in a closed and heat-insulated container with areas of different concentrations is investigated in a similar way. After these three investigations the explanation for the direction of time can be given. Furthermore, an explanation for the heat flow from "hot" to "cold" as well as for the diffusion flow during concentration equalization is given.